Intryga w języku. O knuciu i knowaniu z perspektywy genologii lingwistycznej = Intrigue in language. On plotting and scheming from the perspective of linguistic genology - Kalisz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An intrigue has been made the subject of this article - an extremely complex form with a perverse communicative intention. With the use of the linguistic genology tools and support of communication studies, the specific nature of this genre was captured, which as a collection of freely occurring structures (conversation, gossip, lie or dispute), takes the form of a meticulously designed communicative event.
Keywords: intryga; intrygant; gatunek mowy; kolekcja gatunków; wartość; intrigue; intriguer; speech genre; genre collection; values